Mathematics Achievement in Secondary Education Examination at Diktel Rupakot Majhuwagadhi Municipality, Khotang - Bista Chhetri, Padam Bahadur (DMC Journal, 2024)
This study is undertaken to assess gender(boy and girl), school type [Community School (CS) and institutional school (IS)] and parent condition [parents living together (PLT) and parent living separately (PLS)] differences in mathematics GPA in theory (MG). Data are collected by interview schedule, grade sheet of results of the 2080 Secondary Education Examination (SEE) and from school records. The accessible population was class 10 students from secondary schools in Diktel Rupakot Majhuwagadi Municipality (DRMM) in Khotang District. Five CS and Two IS are selected for the sample purposively. 348 students are selected by census method from sampled school and their grade sheets are downloaded. Out of 348 students, 198 are boys and 150 are girls, 260 students are from CS and 88 students are from IS 195 students studied staying with parents and 153 students studied without staying with parents. Information about gender, school type and parent condition is collected through interviews with head teachers, and mathematics teachers and from school records. It is found that grade grade-wise result of SEE 2080 of DRMM is better than the national level, there is no gender difference in MG of SEE 2080 of DRMM, and there is a significant difference in MG between CS and IS students. Specifically, MG of IS are better than MG of CS, there is a significant difference in MG between PLT and PLS students. Specifically, the Mean of MG of PLT is more than PLS. Findings suggest that educational planners, educators, administrators, parents, teachers and students create an environment of teaching-learning of mathematics like IS in the CS. Parents try to stay with their children and teachers should give more focus to those students who do not stay with their parents while teaching mathematics.